2017
DOI: 10.1016/j.jhazmat.2016.04.075
|View full text |Cite
|
Sign up to set email alerts
|

Airborne engineered nanomaterials in the workplace—a review of release and worker exposure during nanomaterial production and handling processes

Abstract: For exposure and risk assessment in occupational settings involving engineered nanomaterials (ENMs), it is important to understand the mechanisms of release and how they are influenced by the ENM, the matrix material, and process characteristics. This review summarizes studies providing ENM release information in occupational settings, during different industrial activities and using various nanomaterials. It also assesses the contextual information - such as the amounts of materials handled, protective measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 68 publications
1
72
0
1
Order By: Relevance
“…Despite relatively extensive mining and industrial use of HNTs and the possibility that a fraction of the HNTs may fulfil the fiber paradigm, we were not able to find occupational exposure studies considering occupational exposure to HNTs (Debia et al, 2016;Ding et al, 2017). In this study, we showed that pouring of ca.…”
Section: Risk Assessmentmentioning
confidence: 70%
“…Despite relatively extensive mining and industrial use of HNTs and the possibility that a fraction of the HNTs may fulfil the fiber paradigm, we were not able to find occupational exposure studies considering occupational exposure to HNTs (Debia et al, 2016;Ding et al, 2017). In this study, we showed that pouring of ca.…”
Section: Risk Assessmentmentioning
confidence: 70%
“…If nanomaterials cannot be released from a product matrix in any way (Wohlleben et al 2011a; Bräu et al 2012; Ding et al 2017), these qualifiers may serve to justify the waiving of testing (Arts et al 2015). …”
Section: Decision-making Framework For the Grouping And Testing Of Namentioning
confidence: 99%
“…The superb physicochemical properties of manufactured nanomaterials (NMs) greatly facilitate their increasingly wide-spread use in medicine and industry which has led to exponential growth of NM-containing industrial products over the past decades. 1,2 Large-scale manufacturing of NMs substantially increased the risks for human health especially but not limited to occupational settings 3 resulting in the release of new guidelines by the World Health Organization (WHO) to protect workers from the potential risks of NMs. 4 In particular, respiratory inhalation of NMs and/or nanosized ambient particulate matter is a major public concern mainly associated with cardiovascular and pulmonary morbidity and mortality.…”
mentioning
confidence: 99%